Is Lesion of Exner’s Area Linked to Progressive Agraphia in Amyotrophic Lateral Sclerosis with Dementia? An Autopsy Case Report - Kenji Ishihara; Hiroo Ichikawa; Yoshio Suzuki; Jun’ichi Shiota; Imaharu Nakano; Mitsuru Kawamura (Behavioural Neurology, 2010)
Agraphia, as a neuropsychological symptom of ALS, especially ALS with dementia (ALS-D), has recently attracted more attention. However, the brain lesion responsible has not been identified. Here we present an autopsy case of ALS-D of a patient with obvious agraphia, without aphasia, that also presented cerebrospinal degeneration with TDP-43-pathology compatible with ALS-D. Of the pre-motor frontal lobe cortices, degeneration and immuno-histochemical pathology were most obvious in the caudal area of the left middle frontal gyrus, or Exner’s area. Assuring this area plays a pivotal role in the kanji and kana formation used in writing the Japanese language, this case of ALS-D showed both agraphia and Exner's area stressed pathological lesions. It may thus be the first case to indicate an intimate relationship between the neuropsychological symptoms and an associated lesion for ALS-D.